Evaluation of the effectiveness methods of initial pilots’ proffessional training to operate the aircraft equipped with electronic flight instrument systems - S. G. Kosachevskiy; D. V. Aidarkin; D. V. Kachan (Научный вестник МГТУ ГА, 2018)
Nowadays, educational institutions carrying out pilots’ training in the Russian Federation use completely new generation aircraft different with high degree of control automatisation (EFIS – Electronic Flight Instrument System). At the same time, the applied methods of flight training are based on studies carried out for aircraft with analog instruments, which does not allow to use new generation aircraft and simulators wide possibilities at  their full capacity. Therefore, there is a vital necessity of enhancing the method of pilots’ initial professional training that should contain teaching rational methods of distribution and switching visual attention. In 2017 in accordance with the Order of the Federal Air Transport Agency of the Russian Federation in the Ulyanovsk Institute of Civil Aviation a complex of research was carried out that allowed developing the method of initial pilots’ flight training on the aircraft equipped with EFIS. During the research, the oculometric research methods of cadets’ distribution and switching attention (the "eye-tracking" technology) were used, which allowed a deeper study of the piloting skills formation and their impact on pilot's operation with EFIS. To assess the effectiveness of the developed methods, two series of experiments involving cadets of Ulyanovsk Institute of Civil Aviation and its branch in Sasovo were conducted. Two types of simulators: L-410 and Diamond 40 NG were used for research purposes. In this article it is proposed to use the correlation coefficient and the Manhattan distance to assess the accuracy of maintaining flight parameters during cadet simulator training. According to the results of the first series of experiments, it was found out that the cadets under the experiment showed a lower level of flight training compared to the control group of cadets. However, after training the group under the experiment on the developed method, a level of flight preparation in the both groups became equal. Statistically significant differences of initial and final levels of flight training for the cadets of the experimental group were observed while cadets of a control group completed the series of experiments without any significant changes. The second series of experiments revealed that the lack of flight practice among the cadets of the experimental group did not prevent them from demonstrating a qualitative level of professional training when practicing on the flight simulator. Such a result was achieved due to the ground preparation of cadets on the developed method what, undoubtedly, indicates its effectiveness.